Angiotensin (1–7) Improves Pancreatic Islet Function via Upregulating PDX-1 and GCK: A Dose-Dependent Study in Mice - Ziwei Lin; Jiaqi Lin; Anqi Huang; Zixu Zhang; Xinyi Wu; Guoshu Yin; Chiju Wei; Wencan Xu (International Journal of Endocrinology)
Conclusion: Angiotensin (1–7) could improve glucose and lipid metabolism and islet function by promoting the expression of PDX-1 and GCK genes in the pancreas of db/db mice.